Delegitimization of Electoral Democracy: the Effects of Modern Political Communication - Beznosov, Mikhail (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
This article is an attempt to analyze the reasons for negative effects of political communication modernization on contemporary electoral democracy. The analysis makes it evident that one of the main problems of the democracy nowadays is the contradiction between modernization of politics in contemporary world and challenges that this modernization poses to the democratic legitimacy. Also, there was demonstrated that and poor functioning of political institutions is a consequence of current political modernization, which is not capable of the adequate response to the challenges of the radical social changes.